GROSSE AKTA YANG DIBUAT NOTARIS SEBAGAI PENGAKUAN HUTANG DALAM PERJANJIAN KREDIT PADA BANK RAKYAT INDONESIA KCU SAMARINDA - rolland palyndho bentenusa (Journal of Law ( Jurnal Ilmu Hukum ), 2015)
ABSTRACT              In the application or implementation is not easy to determine whether the proposed grosse deed has met the formal and material requirements. Especially with regard to the material requirements of the grosse deed. In practice many problematic because of developments in society for grosse deed which is based on a credit agreement of the bank as the principal agreement. Grosse deed of acknowledgment of debt agreements overlaid with another form of authority or power to sell and install security rights and others in one grosse deed is not allowed because it causes rancaunya in execution, namely whether the execution was carried out against grosse deed of acknowledgment of debt or on the certificate of encumbrance , So this law infringe the rules set forth in article 224 HIR and fatwa MA No. 213/229/85 / UM-TU / Pdt April 16, 1985 so grosse aktapengakuan debt was not pure recognition of the debtor debts to creditors a certain amount and cause of the debt recognition grosse deed null and void and the implementation of the execution can not be carried out. And the payment in installments, interest and penalties and other costs to the cost of execution that is overlaid in a debt recognition grosse deed can not be justified according to the nature of the deed grosse should be purely unilateral declaration of debituryang recognize certain amount of money owed to creditors that after with the rules in Article 224 HIR and fatwa MA No. 213/229/85 / UM-TU / Pdt April 16, 1985, while pencamtuman clause on payment in installments, interest and penalties and other costs to the cost of execution should be included in the loan agreement only. The execution procedure debt recognition grosse deed should not melaluiPengadilan State, but in practice serung case that an application for debt recognition grosse certificate must first pass through the court process and can not be directly dimihonkan grosse execution of the deed of acknowledgment of debt and it will take a long time. While the government bank Bank Rakyat Indonesia Branch Samarinda then be handed over to KP2LN and PUPN, however if the instasi filed a lawsuit to the District Court then the Court should not be refused on the grounds is not the authority of the Court.